STUDI ETNOFARFARMASI PADA SUKU ANAK DALAM (SAD) DI DESA PEMAYONGAN KECAMATAN SUMAY KABUPATEN TEBO PROVINSI JAMBI: STUDI ETNOFARFARMASI PADA SUKU ANAK DALAM (SAD) DI DESA PEMAYONGAN KECAMATAN SUMAY KABUPATEN TEBO PROVINSI JAMBI - Santi Perawati; Deny Sutrisno (Balitbangda Provinsi Jambi, 2023)
Background : Suku Anak Dalam is one of the tribes in Indonesia who still upholds their customs and culture, including their local knowledge about medicine using medicinal plants. One of the Suku Anak Dalam community lives in Pemayongan Village, Tebo Regency, Jambi Province. This ethnopharmaceutical research was conducted to find out various diseases experienced by Suku Anak Dalam and to know various natural resources that are used as treatment. Method : This type of research is a descriptive study using qualitative methods and sampling techniques, namely snowball sampling through open-ended interviews with informants. Results: The results of the study stated that diseases that was often experienced by the Suku Anak Dalam included fever, coughing, itching, shortness of breath and abdominal pain. Treatment of the disease by utilizing natural resources in the form of plants and animals. Plant parts used are roots, leaves, bark, and fruit sap, while for animals the parts used are fat, scales, and meat. The processing method is scraped, crushed, boiled, fried, while the use of these ingredients is eaten, drunk, and applied to the affected part. Conclusion : Based on the results of research that has been done there are 5 diseases that often occur and there are 9 kinds of plants and 5 animals that are used as traditional medicine. Keywords : Ethnopharmacy, Disease, Jambi, Suku Anak Dalam, Natural Resources